2015
DOI: 10.1152/ajpendo.00264.2015
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of REDD1 gene ameliorates sepsis-induced decrease in mTORC1 signaling but has divergent effects on proteolytic signaling in skeletal muscle

Abstract: Steiner JL, Crowell KT, Kimball SR, Lang CH. Disruption of REDD1 gene ameliorates sepsis-induced decrease in mTORC1 signaling but has divergent effects on proteolytic signaling in skeletal muscle. Am J Physiol Endocrinol Metab 309: E981-E994, 2015. First published October 20, 2015 doi:10.1152/ajpendo.00264.2015.-Sepsis-induced skeletal muscle atrophy and weakness are due in part to decreased mTORC1-mediated protein synthesis and increased proteolysis via the autophagy-lysosomal system and ubiquitin-proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 56 publications
3
26
1
Order By: Relevance
“…Consistent with this idea, a study by Lafarge and coworkers demonstrated that the livers of mice deficient for the protease cathepsin S exhibited a lower rate of hepatocellular respiration compared with control counterparts, concomitant with elevated hepatic expression of REDD1 [77]. In addition, peritoneal sepsis has been reported to increase REDD1 protein content in skeletal muscle of mice [78], as well as to promote derangements in mitochondrial bioenergetics in this tissue [79]. Therefore, further work will be required to explore the potential link between obesity and/or diabetes, REDD1, and mitochondrial function, for example using relevant animal models of obesity and/or diabetes as well as REDD1 deficiency.…”
Section: Redd1-mediated Regulation Of Mitochondrial Functionmentioning
confidence: 79%
“…Consistent with this idea, a study by Lafarge and coworkers demonstrated that the livers of mice deficient for the protease cathepsin S exhibited a lower rate of hepatocellular respiration compared with control counterparts, concomitant with elevated hepatic expression of REDD1 [77]. In addition, peritoneal sepsis has been reported to increase REDD1 protein content in skeletal muscle of mice [78], as well as to promote derangements in mitochondrial bioenergetics in this tissue [79]. Therefore, further work will be required to explore the potential link between obesity and/or diabetes, REDD1, and mitochondrial function, for example using relevant animal models of obesity and/or diabetes as well as REDD1 deficiency.…”
Section: Redd1-mediated Regulation Of Mitochondrial Functionmentioning
confidence: 79%
“…Activating the Akt-TSC2-mTORC1 pathway appears to represent a compensatory upregulation during the recovery phase that is capable of enhancing protein synthesis via a coordinated increase of both the initiation and elongation phase of translation. The activation of this canonical pathway is notable as it represents a complete reversal of the hypo-phosphorylation of Akt, mTOR, 4E-BP1 and S6K1, eIF4B and eEF2K detected acutely in muscle at 24 h after CLP (12, 24). …”
Section: Discussionmentioning
confidence: 99%
“…However, in the recovery phase, AMPK phosphorylation did not differ from control levels and we detected a decrease in total REDD1. Previous studies have indicated that knockdown of REDD1 protein largely prevents the acute sepsis-induced decrease in muscle protein synthesis (12). Moreover, knockdown of REDD1 also activates (phosphorylates) Akt, thereby stimulating mTORC1 (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the REDD1 gene offset the sepsis-induced decrease in mTORC1 signaling [phosphorylation of p70S6K1 (Thr 389 ), 4E-BP1 (Ser 65 ), rpS6 (Ser 240/244 )] and protein synthesis (114). In addition to mediating the sepsis-related modulation of mTORC1 signaling, REDD1 also appeared to contribute to the sepsis-induced increase in autophagy.…”
Section: E162mentioning
confidence: 98%